Deviation from Sale & Purchase Agreement Made by A Notary in Sale of Land - Lita Astika Pangesthi (Sultan Agung Notary Law Review, 2021)
A sale and purchase agreement is an agreement between the seller and the buyer, prior to the execution of the Sale and Purchase Deed. Because there are requirements in the sale and purchase that have not been fulfilled, these requirements include: a certificate of land title is in process, the price has not been paid for the sale and purchase of the land, or because the taxes imposed have not been able to be paid by the seller or the buyer. The purpose of this research is to examine: 1). Implementation of PPJB made by a Notary in buying and selling land, 2). Irregularities and solutions in the implementation of PPJB made by Notaries in the sale and purchase of land. The approach method in this research is Normative Juridical. Legal research is carried out by examining library materials or secondary data as the basic material for research by conducting a search of the regulations and literatures related to the problem under study.Conclusion with the making of the Sale and Purchase Agreement by the Notary Public, in its implementation, legal deviations are not uncommon, among others: 1). PPJB is not always behind the name of the buyer, but is resold to a third party, 2). Transaction value in AJB is not in accordance with PPJB, 3). Authorization to sell for PPJB paid off separately.